8(-2i)(-5-4i)=

Simple and best practice solution for 8(-2i)(-5-4i)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8(-2i)(-5-4i)= equation:


Simplifying
8(-2i)(-5 + -4i) = 0

Remove parenthesis around (-2i)
8 * -2i(-5 + -4i) = 0

Multiply 8 * -2
-16i(-5 + -4i) = 0
(-5 * -16i + -4i * -16i) = 0
(80i + 64i2) = 0

Solving
80i + 64i2 = 0

Solving for variable 'i'.

Factor out the Greatest Common Factor (GCF), '16i'.
16i(5 + 4i) = 0

Ignore the factor 16.

Subproblem 1

Set the factor 'i' equal to zero and attempt to solve: Simplifying i = 0 Solving i = 0 Move all terms containing i to the left, all other terms to the right. Simplifying i = 0

Subproblem 2

Set the factor '(5 + 4i)' equal to zero and attempt to solve: Simplifying 5 + 4i = 0 Solving 5 + 4i = 0 Move all terms containing i to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 4i = 0 + -5 Combine like terms: 5 + -5 = 0 0 + 4i = 0 + -5 4i = 0 + -5 Combine like terms: 0 + -5 = -5 4i = -5 Divide each side by '4'. i = -1.25 Simplifying i = -1.25

Solution

i = {0, -1.25}

See similar equations:

| (8(-3)-1)-(-3)+3= | | 82(0.006889-x^2)=2x | | 3x-3y=4x+5 | | 19=4-2x | | 32x-4=3 | | -16a+11a+7a=-16 | | w/- | | 82(0.006888-x^2)=2x | | -16+y=5 | | 6-a=10-9 | | 4(x-6)=21 | | -3p+13p+14=-16 | | 2*.2-3+7+7+3*.2-10= | | (3x+3)=(4x-5) | | 15(t+2)2+9t=-90 | | 2x+5(.3-2.3)=3 | | r=0.301 | | 12+6r=-4r-5-7r | | y=10*x+500 | | -5x+4-3(x-1)=-3x-(4x-1)+3 | | 13q-12q+q-2=12 | | 1.8x=.25 | | 100=x+10x | | 3x-3(4x+5)=-15 | | n-56=26 | | X^4+2x^2=6x^2 | | -13=3u-4 | | (4y+16)(4y+16)=8 | | 3-1x=6 | | 8e-4(12-5e)=60 | | 5b-6b-3=-11 | | -4(-h)=68 |

Equations solver categories